ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 70/PUU-XXII/2024 TENTANG SYARAT USIA CALON KEPALA DAERAH - Kurniawan, Anfal (Semarang Law Review (SLR), 2024)
In this article the researcher aims to analyse and find out the Constitutional Court's decision number 70/PUU-XXII/2024 in testing Law Number 10 of 2016 concerning the second amendment to Law Number 1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the election of Governors, Regents and Mayors into Law, as for what is referred to as the applicant is as we know referring to Article 51 of the Constitutional Court Law in PUU is a party whose constitutional rights and authorities feel aggrieved before the enactment of the Act, there are conditions for the fulfilment of a form of judicial review of the law with all its authority The Constitutional Court has legitimacy as the holder of judicial power at the first and last level with a constitutional nature. In writing this article, researchers used a normative juridical approach with qualitative data in the form of inferential descriptive analysis sourced from documents, books, and laws. In decision Number 70/PUU-XXII/2024 The decision of the Constitutional Court includes rejecting the petitioner's request for provision as explained in the main petition in the form of rejecting the petition as a whole. The decision of the Constitutional Court is final and constitutional. Therefore, in this analysis at least the researcher analyses the decision of the Constitutional Court. As we know the nature of the constitution is die geschriben verfassung in writing and in essence is rechtsverfassung as grundgesetz.AbstrakDi dalam artikel ini peneliti bertujuan untuk menganalisis dan mengetahui putusan MK nomor 70/PUU-XXII/2024 dalam pengujian Undang-Undang Nomor 10 Tahun 2016 Tentang perubahan kedua atas Undang-Undang Nomor 1 Tahun 2015 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2014 Tentang pemilihan Gubernur, Bupati, dan Walikota menjadi Undang-Undang, adapun yang disebut sebagai pemohon ialah sebagaimana yang kita ketahui merujuk pada Pasal 51 Undang-Undang MK didalam PUU merupakan pihak dimana hak dan kewenangan konstitusionalnya merasa dirugikan dihadapan berlakunya Undang-Undang, terdapat syarat-syarat untuk terpenuhinya suatu bentuk pengujian undang-undang dengan segala kewenangannya Mahkamah Konstitusi memiliki legitimasi sebagai pemegang kekuasaan kehakiman pada tingkat pertama dan terakhir dengan sifat konstitusional. Didalam penulisan artikel ini Peneliti menggunakan pendekatan Yuridis Normatif dengan data kualitatif berupa analisis diskriptif inferensial yang bersumber dari dokumen-dokumen, buku, dan Undang-Undang. Dalam putusan Nomor 70/PUU-XXII/2024 amar putusan Mahkamah Konstitusi mengadili diantaranya menolak permohonan provisi para pemohon dijelaskan sebagaimana dalam pokok permohonan berupa menolak permohonan pemohon secara keseluruhan. Putusan Mahkamah Konstitusi bersifat final dan konstitusional. Oleh karenanya didalam analisis ini sekurang-kurangnya peneliti menganalisis putusan Mahkamah Konstitusi terebut. Sebagaimana yang kita ketahui sifat konstitusi ialah die geschriben verfassung secara tertulis dan pada hakikatnya ialah rechtsverfassung sebagai grundgesetz.